Fungal Contamination of Airconditioner Units in Five Hospitals of Erbil Province- Kurdistan Region /Iraq - Al-Bader, Salah M.; Ismael, Layla Q.; Ahmood, Asaad A. (Science Journal of University of Zakho, 2018)
During April 2018, 75samples were collected from five hospitals in Erbil city. Samples were taken by sterile cotton swabs from the air dispenser window of air conditioner units (ACU) . They were cultured directly on Sabouraud's dextrose agar incubated at 25oC ±2. The samples were collected from five departments in each hospital include out-patient ward (OP),in-patient ward (IP), emergency room (ER), intensive care unit(ICU), and operation theater (OT). A total of (410) fungal colonies were counted, they belong to13 genera include ten hyphomycetes and only one of zygomycetes ,basidiomycetes , and hemiascomycetes. Penicillium represented in the highest total occurrence (40%) followed by Aspergillus(38.66%) and Alternaria (21.33%). The total frequency showed that Candidawas the highest (30%) followed by Penicillium(27.56%) and Aspergillus(13.17%). The highest density of filamentous fungi (no. of colony/sample) was detected in OP=16.75, and the lowest in OT=1.5. The diversity of isolates showed that ( 9) genera were recorded from ER(60%) and only one in OP (6%). All recorded genera in current study were regarded as indoor air pollutants. The predominant genera Alternaria, Aspergillus, Penicillium ,Cladosporiumand Candida are well-known allergens and may cause several pulmonary disorders as well as fetal infections in particular cases.